2015
DOI: 10.1590/1982-0224-20140115
|View full text |Cite
|
Sign up to set email alerts
|

Hematological and morphometric blood value of four cultured species of economically important tropical foodfish

Abstract: The use and validation of fish health monitoring tools have become increasingly evident due to aquaculture expansion. This study investigated the hematology and blood morphometrics of Piaractus mesopotamicus, Brycon orbignyanus, Oreochromis niloticus and Rhamdia quelen. The fish were kept for 30 days in 300-liter aquariums, after which they were anesthetized with benzocaine and blood was collected from caudal vessels. In comparison to other species, B. orbignyanus presented the highest hematocrit (Ht), RBC ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
7
19
0
Order By: Relevance
“…The blood data allow responses to the health status of fish subjected to dietary manipulations. The blood values obtained in the present study are within the documented range for the species R. quelen (Dal’Bó, 2015). However, the diet supplemented with Lys only resulted in an increase in the number of erythrocytes and decrease in MCH and MCV.…”
Section: Discussionsupporting
confidence: 83%
“…The blood data allow responses to the health status of fish subjected to dietary manipulations. The blood values obtained in the present study are within the documented range for the species R. quelen (Dal’Bó, 2015). However, the diet supplemented with Lys only resulted in an increase in the number of erythrocytes and decrease in MCH and MCV.…”
Section: Discussionsupporting
confidence: 83%
“…A minor difference in the values of the mentioned morphometric parameters in this study compared to Adili et al [3,10] is likely to be related to the different ovine breed and breeding methods. Breed, age, and sex are known to affect the values of morphometric parameters [11,24]. In our study, the values of RBC length/diameter are almost equal to those of Thamer et al [25] (5.277 ± 0.67 µm), although in a different sheep breed.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, changes in RBC morphometric indicators have been detected in certain human [4,7,8] and dog ailments [9]. Morphometric studies of RBCs showed several morphological changes; the most important one is due to age and breed in sheep and goats [10], and also in fish [11]. Buslovskaya et al [12] defined a set of changes of several morphometric and functional parameters of RBCs and white blood cells, characteristic of different adaptive reactions of the chicken organism.…”
Section: Introductionmentioning
confidence: 99%
“…Both abiotic factors and life history traits can also affect the composition and morphology of fish RBC (Dal’Bó et al, 2015; Kumar, 2016; Yakhnenko et al, 2016). For example, RBC size is inversely related to swimming ability in teleosts (Lay and Baldwin 1999; Witeska 2013), while size of RBCs is highest at intermediate altitude in one lizard species (González-Morales et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While immature RBC (erythroblasts) are usually rounded, older cells are fusiform (Fijan 2002, Passantino et al 2004). However, the degree of ellipticalness seems to vary among species (Dal’Bó et al, 2015). However, little is known about the physiological implications of the variation in the fusiform shape for species.…”
Section: Introductionmentioning
confidence: 99%